Blicke in den Spiegel des Koran Sufische Koraninterpretationen der Gegenwart - Hentschel, Yunus Valerian (2023)
Sufis interpret the Qur'an in creative ways closely related to their life-experiences. The analysis of fourteen interviews with Sufis from diverse teaching traditions and cultural backgrounds gives insight into these Sufis' ethic-spiritual efforts for a purification of their selves with the aim to come closer to God. The resulting process-related, selfreflective forms of engagement with the Qur'an lead to original socioreligious perspectives.